Discussion (Scottish Historical and Archaeological Internet Reports, 2013)
Documentary evidence records that at least four tenements were compulsorily purchased. Building work for the Tron Kirk would have destroyed these. It has been possible to identify some of the owners of these tenements and some of the functions to which the buildings were put. Documentary and archaeological evidence are drawn together to form a narrative of sorts for each building.